The Potential Utilization of Aromatic Plants in Kembang Kuning Resort, Gunung Rinjani National Park, West Nusa Tenggara - Vina Savinatus Sa'adah; Ervizal A. M. Zuhud; Siswoyo Siswoyo (Department of Forest Resources Conservation and Ecotourism - IPB University, 2019)
Gunung Rinjani National Park (TNGR) is nature conservation area located in West Nusa Tenggara. Kembang Kuning Resort is one of the TNGR‘s resorts under Territory Management Section (SPW) II East Lombok which has high potential for biological diversity which one of them is aromatic plants. Aromatic plants are plants that produce essential oils. dentify the diversity of aromatic plant species, and ethnobotany aromatic plants in communities around the area. The methods used are the vegetation analysis, terpenoid phytochemicals test and interviews. The results of the vegetation analysis found 47 species from 28 families of aromatic plants including six widely known species and 41 potential species. The widely known species which are the species that used by the community, have economic value, and there have been many studies related to these species, while potential aromatic plants are plants that have been tested phytochemical and positively have terpenoids but have not had the market value and not widely known by the community. Aromatic plants are used as medicine for both external diseases and internal diseases, religious rituals and beliefs, pesticides, cooking spices, and fragrances. Keywords: aromatic, diversity, ethnobotany, plants, species